2000
DOI: 10.1302/0301-620x.82b6.10740
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of bone marrow oedema on MRI in osteonecrosis of the femoral head

Abstract: It has been suggested that transient osteoporosis or the bone marrow oedema syndrome (BMOS) may be the initial phase of osteonecrosis of the femoral head (ONFH) and that there may be a common pathophysiology. In this study, we have assessed the MR images of 200 consecutive patients with ONFH in respect of the BMO pattern in order to test this hypothesis. This pattern was not observed in the early stage of ONFH. The initial abnormal finding detected on the MR images was an abnormal band of intensity at the junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 21 publications
(12 reference statements)
0
20
1
1
Order By: Relevance
“…It appears that ESWT induces NO production and promotes angiogenesis and osteogenesis, and anti-inXammatory responses that are complimentary in the treatment of hip necrosis. The severity of hip pain in ONFH often is associated with the degree of bone marrow edema, and many cases showed decreased hip pain with reduced bone marrow edema after ESWT [12,21]. Bone marrow edema may represent an inXammatory process during the natural course in the development of ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that ESWT induces NO production and promotes angiogenesis and osteogenesis, and anti-inXammatory responses that are complimentary in the treatment of hip necrosis. The severity of hip pain in ONFH often is associated with the degree of bone marrow edema, and many cases showed decreased hip pain with reduced bone marrow edema after ESWT [12,21]. Bone marrow edema may represent an inXammatory process during the natural course in the development of ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a relationship between transient BME and avascular necrosis [2,[24][25][26], but the incidence of progression from BME to avascular necrosis is still unclear. Furthermore there is still controversy as to whether ischemic BMES reflects a distinct self-limiting disease [27,28] or a kind of reflex sympathetic dystrophy [29,30].…”
Section: Bmes Was First Described In 1959 By Curtiss Andmentioning
confidence: 99%
“…A similar study showed that a band pattern is the initial MR imaging finding of early ON without any prior diffuse BME depicted [39]. BME appears to exist with a peak occurrence in advanced stage of the disease [37,40]. In another study, BME developed after the onset of hip pain and correlated significantly with the subsequent collapse of the femoral head suggesting progression to advanced ON [41] (Fig.…”
Section: Differential Diagnosis Of On and Tohmentioning
confidence: 76%
“…4). It has been shown that patients with ON of the femoral head do not have findings of BME typical for TOH in the early stages of the disease [37]. In a study presenting early findings in ON, BME was never found before the appearance of band patterns, suggesting that the latter are actually the initial ON changes which are not expected in TOH [38].…”
Section: Differential Diagnosis Of On and Tohmentioning
confidence: 94%